Potential use of composts and vermicomposts as low-cost adsorbents for dye removal: an overlooked application - Paradelo, Remigio; Vecino, Xanel; Moldes, Ana Belén; Barral, María Teresa (Environmental science and pollution research international, 2019)
The use of composts and vermicomposts as adsorbents is an important topic of study in the field of environmental remediation. These materials are rich in organic matter and have functional groups that can interact with organic and inorganic compounds. They also contain microorganisms that can promote biodegradation of organic substances. Composts that cannot be used for agronomic purposes (owing to e.g. low nutrient levels or phytotoxicity) may be valuable for soil remediation or pollutant removal. In this review, we discuss papers on this topic, with the objective of drawing attention to the potential use of composts/vermicomposts and to recommend further investigation on this subject. Few published studies have investigated the use of composts/vermicomposts to remove dyes and other coloured compounds. However, preliminary results show that these materials are potentially good adsorbents, at least comparable to other low-cost adsorbents, and that, in general, basic dyes are more efficiently removed than direct, reactive or acid dyes. The results of the works reviewed also show that dye removal takes place by adsorption mechanisms, in most studies following a Langmuir model, and that the kinetics of removal are fast and follow a pseudo-second order model. However, there remain several uncertainties regarding this application. For example, very few dyes have been studied so far, and little is known about the influence of the properties of composts/vermicomposts on the dye removal process. Moreover, the possible use of compost/vermicompost to enhance biodegradation processes has not been explored. All these questions should be addressed in future research.